2001
DOI: 10.1063/1.1320009
|View full text |Cite
|
Sign up to set email alerts
|

Electron field emission for ultrananocrystalline diamond films

Abstract: Microstructure and its effect on field electron emission of grain-size-controlled nanocrystalline diamond films Ultrananocrystalline diamond ͑UNCD͒ films 0.1-2.4 m thick were conformally deposited on sharp single Si microtip emitters, using microwave CH 4 -Ar plasma-enhanced chemical vapor deposition in combination with a dielectrophoretic seeding process. Field-emission studies exhibited stable, extremely high ͑60-100 A/tip͒ emission current, with little variation in threshold fields as a function of film thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(93 citation statements)
references
References 36 publications
1
82
0
4
Order By: Relevance
“…5a, exhibits the characteristic features of diamond [42], namely the edge jump at ~289.0 eV, the exciton peak at ~289.3 eV, and the second band gap at ~302.5 eV. All these features are due to the C 1s → σ* transition for sp 3 -hybridized carbon-carbon bonds in the crystalline diamond configuration. Besides the characteristic peaks of diamond, a small absorption band at 285.0 eV was detected.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…5a, exhibits the characteristic features of diamond [42], namely the edge jump at ~289.0 eV, the exciton peak at ~289.3 eV, and the second band gap at ~302.5 eV. All these features are due to the C 1s → σ* transition for sp 3 -hybridized carbon-carbon bonds in the crystalline diamond configuration. Besides the characteristic peaks of diamond, a small absorption band at 285.0 eV was detected.…”
Section: Resultsmentioning
confidence: 95%
“…[1][2][3] While maintaining most of the exceptional physical/chemical properties of conventional diamond materials, UNCD has an extremely low grain size (3-5 nm) and roughness (sub-10 nm) independent of thickness, which drives its popularity as an engineering and functional martial, especially in the fields of tribology, biology, and micro/nano-technology. [4][5] In conventional polycrystalline diamond coatings, for either nanocrystalline diamond (NCD) or microcrystalline diamond (MCD), the gas composition usually consists of CH 4 or other carbon source with majority of hydrogen gas in a chemical vapor deposition (CVD) reactor.…”
Section: Introductionmentioning
confidence: 99%
“…Such breakdown behavior is strongly affected by the geometry (corners) and surfaces (roughness, work function) of the gap structures; hence small process variations and defects could lead to catastrophic failure of higher frequency devices. Although it has been shown that UNCD exhibits good electric field-induced electron emission, this only occurs at high vacuum levels of about 10 −6 to 10 −8 Torr [42]. Conversely, the dc characterization of UNCD-based resonators is done at atmospheric pressure where the mean free path of any electron emitted from the UNCD surface is negligible and therefore electrons would not be emitted or accelerated from that surface.…”
Section: Electrostatically Actuated Uncd-based Mems Resonatorsmentioning
confidence: 99%
“…Other applications make use of the large aspect ratio of NWs and their sharp tips, which enable semiconductor NWs to be used as field emitters. [8][9][10] In contrast to the aforementioned applications, in this paper we will show how to employ the metal catalyst atop VLS NWs for sensing, making use of the surface-enhanced Raman scattering (SERS) effect. [11][12][13] SERS is an experimental technique that is nowadays used to detect extremely small quantities of molecules by determining their characteristic Raman signal, that is, their characteristic vibrational modes.…”
Section: Introductionmentioning
confidence: 99%